(untitled) (Revista de Ciências Agroveterinárias, 2006)
The bramble-holy (Maytenus ilicifolia) received that name exactly by the appearance of their leaves, which introduce thorns in the margins and to for being a “holy medicine” for the several problems treatment. It is a tree, of small postage, growing 5 m of height, endowed of round and dense cup, native of regions of southern altitude of Brazil. Leaves cornices and brilliant, with margins resulted from of thorns little rigid. Your great utility, however, is in the homemade medicine, where has been long date maid in the treatment of stomached problems, gastritis and ulcers. In DF popular commerce were collected 12 bramble samples - holy for sale, however, can observe, which the offered species is not Maytenus ilicifolia (Celastraceae), and yes, provable, Sorocea bomplandii (Moraceae), or another Maytenus’ Species, used in the adulteration of the bramble-holy. By means of that, the goal of this research was to verify the botanical change of the bramble - fairs arising holy and Brazilia-DF Raiders and to verify if the therapeutic indication is in agreement with the use recognized by the scientific literature. To the final of this investigation, that was observed there are expressive differences among collected samples and the standard drug, concluding itself that the popularly commercialized species as bramble-holy in the Distrito Federal does not correspond to Maytenus ilicifolia.